(3GTGQGJ GdCUhds - (3eMeO Hf EHQGgje Hf eMeO MSf GdCUagGfj GdcQHGSj,J (B1260 (3g` s
(3ChdgG (B:s
(3GdefgL GdeYGT ai GdCOdI GdTQYjI s
(3BNQgG (B:s
(3hCcdJ JQGH GdCQV WhGd YeQi hTQH eGA GdQeGO s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B305 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B216s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B83s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(1246) s
Keywords: (3abg GdePGgH GdCNQis